Atrial Fibrillation: An Underlying Trigger of Cryptogenic Stroke - Nichols, Emma Hitt (MD Conference Express, 2014)
Stroke is a serious condition that can result in substantial morbidity and mortality. It is the number one cause of disability and the second-most common cause of death in the world [World Health Organization.The Atlas of Heart Disease and Stroke 2004]. A major underlying cause of stroke in many patients is atrial fibrillation (AF). This article discusses the role of AF in cryptogenic stroke.